2014
DOI: 10.1155/2014/942978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surfactants on the Properties of Mortar Containing Styrene/Methacrylate Superplasticizer

Abstract: The physical and mechanical properties of mortar containing synthetic cosurfactants as air entraining agent are investigated. The cosurfactants consist of a combination of 2% dodecyl benzene sodium sulfonate (DBSS) and either 1.5% polyvinyl alcohol (PVA) or 1.5% polyoxyethylene glycol monomethyl ether (POE). Also these cosurfactants were used to prepare copolymers latex: styrene/butyl methacrylate (St/BuMA), styrene/methyl methacrylate (St/MMA), and styrene/glycidyl methacrylate (St/GMA), in order to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…PVA, as an anionic action of surfactant, consists of a hydrophobic backbone and a hydrophilic end. The negative charged hydrophobic end can attach on the surface of cement particles with positive charge due to the electrostatic attraction, which benefits to reduce the surface tension and generate stable bubbles in cement matrix, as shown in Figure . Due to the moderate surfactant properties and viscoelasticity of PVA, air bubbles in the cement matrix are hardly to be removed, which can increase the porosity and improve the thermal insulation property of cement paste.…”
Section: Resultsmentioning
confidence: 99%
“…PVA, as an anionic action of surfactant, consists of a hydrophobic backbone and a hydrophilic end. The negative charged hydrophobic end can attach on the surface of cement particles with positive charge due to the electrostatic attraction, which benefits to reduce the surface tension and generate stable bubbles in cement matrix, as shown in Figure . Due to the moderate surfactant properties and viscoelasticity of PVA, air bubbles in the cement matrix are hardly to be removed, which can increase the porosity and improve the thermal insulation property of cement paste.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in air content values of L-arginine-containing cement mortar is due to the increase in the interfacial effect between non-hydrated cement particles and L-arginine. L-arginine acts as an acid-base cationic surfactant where it reduces the surface tension and allows the formation of stable bubbles [42][43][44][45] on the surface of the cement and sand particles. Thus, flow and air content are increased with addition of L-arginine in cement mortar.…”
Section: Flow/slump and Air Content Of Fresh Cement Mortarmentioning
confidence: 99%
“…Negim et al (2019) synthesized a copolymer by grafting 2-EHA on PVA using APS as a free-radical initiator and subsequently found that the properties of the cement improved with increasing the 2-EHA/grafted copolymer ratio. Negim et al (2014Negim et al ( , 2016 investigated the physico-mechanical properties of mortar containing the following cosurfactants: 2-wt.% dodecyl benzene sodium sulfonate (DBSS) and either 1.5-wt.% PVA or 1.5-wt.% polyoxyethylene glycol monomethyl ether (POE) as an air entraining agent. Additionally, the latex copolymers: styrene/butyl methacrylate (St/BuMA), styrene/methyl methacrylate (St/MMA), styrene/glycidyl methacrylate (St/GMA), and styrene/butyl acrylate (St/BuA) were prepared by emulsion in the presence of the abovementioned cosurfactants.…”
Section: Introductionmentioning
confidence: 99%